Inca architecture : the function of a building in relation to its form - Pigeon, Ginger (My University, 2011)
This thesis provides research and information on various architectural constructions at four Inca sites in the Sacred and Urubamba Valleys of Peru: Cuzco, Saqsaywaman, Ollantaytambo, and Machu Picchu. It evaluates the relationship between construction technique and each structure's use, function, and significance within Inca culture. Specifically, architectural elements of the various structures are examined and classified, relative to the following categories: 1) function, 2) structure/form, 3) construction, 4) size, 5) frequency, and lastly, 6) layout. Through a systematic comparison of the sites, this thesis concludes that though all the sites were elite in Inca society, their construction varied in quality. A final analysis demonstrates that these sites follow primarily a hierarchy of construction, and that their function does relate to their form.
Keywords: Cuzco (Peru : Province) -- Antiquities.; Machu Picchu Site (Peru); Incas -- Antiquities.; Excavations (Archaeology) -- Peru.; Archaeology and history.; Archaeology -- Methodology.